HUBUNGAN AKTIVITAS FISIK DENGAN TINGKAT STRES PADA PASIEN DIABETES MELITUS DI PUSKESMAS GONDOKUSUMAN 1 KOTA YOGYAKARTA - Ni Made Winda Opelya; Adi Sucipto; Santi Damayanti; Siti Fadlilah (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2020)
ABSTRACT Stress is a condition that is mostly felt by patients with diabetes mellitus. It is important to control stress level in patients with DM appropriately. One of them is managing daily physical activity in DM patients, through physical activity by releasing energy from skeletal muscle so that it can control high blood sugar which can cause stress in DM patients.To know the relationship of physical activity with stress level of DM patients 1, Yogyakarta City. This research is a kinf of quantitative research with analitic survey method and retrospective design. The sampling technique used was accidental sampling with 34 respondents from 13th until 27th on Mei and used google form on whatsapp application for data resume. The research instrument used was questionnaire of IPAQ and DASS. Analysis of research data used chi square. Most respondent in the category of lack physical activity that is 18 (52,9%.) respondent. The majority of respondent experienced stress, and have category of moderate stress that is 12 (35,3%) respondent. Statistic test result using chi square with ρ value=0,002 (<0,05). There is relationship between physical activity with stress level of DM patients in Puskesmas Gondokusuman 1, Yogyakarta City.